AFET SONRASI SPORCULARIN SPORDA PSİKOLOJİK İHTİYAÇ DURUMLARI İLE AFET TUTUMLARI ARASINDAKİ İLİŞKİNİN İNCELENMESİ (ADIYAMAN İLİ ÖRNEĞİ) - Fırat, Yusuf; Murathan, Fatih; Dalga, Dilay (Nigde Omer Halisdemir University, 2024)
Bu araştırma ile afet bölgesinde 06 Şubat 2023 depremini yaşayan sporcuların temel psikolojik ihtiyaçlarının belirlenmesi ile afete ilişkin tutumlarının psikolojik ihtiyaçlarına etkisinin incelenmesi amaçlanmıştır. Bu ana amaç doğrultusunda sporcuların farklı değişkenlere göre temel psikolojik ihtiyaçlarının değerlendirilmesi de alt amaçları oluşturmaktadır. Araştırma evrenini 06 Şubat 2023 depremlerini yaşayan Adıyaman ilindeki herhangi bir spor branşına kayıtlı lisansı bulunan 17-35 yaş aralığındaki sporcular oluşturmaktadır. Örneklem grubunu ise 06 Şubat 2023 depremlerini yaşayan Adıyaman ilindeki Futbol, Basketbol, Voleybol, Okçuluk, Atletizm, Savunma Sporları, ve Güreş spor branşlarında sporcu lisansına sahip 266 erkek 172 kadın sporcu oluşturmaktadır. Araştırmada veri toplama aracı olarak Karaşin ve ark. (2023) yılında gerçekleştirdikleri “Depreme Yönelik Tutum Ölçeği” ile Sarı ve ark. (2022) yılında gerçekleştirdikleri “Sporda Psikolojik İhtiyaç Durumları Ölçeği” kullanılmıştır. Ayrıca araştırmada araştırma grubunun demografik özelliklerinin belirlendiği sporcu bilgi formu kullanılmıştır. Araştırma sonucunda araştırmaya katılan sporcuların depreme yönelik tutumları ile sporda psikolojik ihtiyaç düzeyleri arasında pozitif yönde ortanın üzerinde ilişki olduğu tespit edilmiştir (r=.667). Dolayısıyla sporcuların depreme yönelik tutum puanları arttıkça sporda psikolojik ihtiyaç düzeyleri de arttığı gözlenmiştir. Araştırmada sonuç olarak deprem bölgesinde yaşayan sporcuların sporda psikolojik ihtiyaç düzeylerinin ortanın üzerinde olduğunun gözlenmesi sporcuların dikkat, algı, motivasyon gibi psikolojik faktörlerin geliştirilmesine yönelik destek çalışmalarına ihtiyaç duyduğu sonucuna varılmıştır.

This research aims to determine the basic psychological needs of athletes who experienced the February 6, 2023 earthquake in the disaster region and to examine the effects of their attitudes towards the disaster on their psychological needs. In line with this main objective, the evaluation of the basic psychological needs of athletes according to different variables constitutes the sub-objectives. The research universe consists of athletes between the ages of 17-35 who are registered and licensed in any sports branch in the Adıyaman province that experienced the February 6, 2023 earthquake. The sample group consists of 266 male and 172 female athletes who have athlete licenses in the sports branches of Football, Basketball, Volleyball, Archery, Athletics, Self-Defense Sports, and Wrestling in the Adıyaman province that experienced the February 6, 2023 earthquake. The “Attitude Towards Earthquake Scale” conducted by Karaşin et al. (2023) and the “Psychological Needs States Scale in Sports” conducted by Sarı et al. (2022) were used as data collection tools in the research. In addition, the athlete information form, which determined the demographic characteristics of the research group, was used in the study. As a result of the research, it was determined that there was a positive relationship above average between the attitudes of the athletes participating in the research towards earthquake and their psychological need levels in sports (r=.667). Therefore, it was observed that as the attitude scores of the athletes towards earthquake increased, their psychological need levels in sports also increased. As a result of the research, it was concluded that the psychological need levels of the athletes living in the earthquake region were above average and that athletes needed support studies to develop psychological factors such as attention, perception and motivation.
EXAMINATION OF THE RELATIONSHIP BETWEEN PSYCHOLOGICAL NEEDS OF ATHLETES IN SPORTS AND THEIR DISASTER ATTITUDES AFTER DISASTER (ADIYAMAN PROVINCE EXAMPLE)
Keywords: Clinical Sciences (Other); Klinik Tıp Bilimleri (Diğer)